(untitled) (European Journal of Health Research, 2019)
The purpose of this article is to determine the process of training in school health and safety by studying the facilitating factors that make it possible to integrate a culture of occupational risk prevention in schools. To this end, a qualitative methodology was used, specifically, a research process called "non-interactive analytical documentary content" was applied for the analysis and interpretation of data extracted from educational experiences recorded in documents, normative-legislation, institutional campaigns and educational-healthy intervention projects promoted by different public and/or private institutions. Finally, it should be pointed out that one of the main conclusions of this study is the need to design a training process that encourages reflection and cooperation between the different public and private institutions, since this allows for feedback on the didactic and organisational mechanisms of the school put into practice, thus obtaining a reference point in the system of socio-labour relations that makes it possible to improve possible future training actions and, above all, to locate such relations in terms of quality and continuous improvement.